Arctic charr (Salvelinus alpinus) farming in southern Norway - Olk, Tom Robin (University of South-Eastern Norway, 2021)
Arctic charr (Salvelinus alpinus) is a stenothermic cold-water fish with a circumpolar distribution. The species features large variations in life history, as populations are anadromous, riverine or lake dwelling. It occurs in various different morphs, which differ in physical traits, such as body size, head shape, and mouth position. The ecological niches of different morphs exhibit great variation as well, e. g. in terms of feeding ecology. Arctic charr has potential as a cultured species, and interest in Arctic charr farming existed since the 1970s. The global production of Arctic charr in aquaculture was between 6000 and 10 000 tonnes in 2013, with all the largest producers located in northern Europe. Arctic charr is suitable for aquaculture, as it grows rapidly at low temperatures, and tolerates high stocking density. Its high fillet yield and amenability to niche markets are also advantageous. However, Arctic charr aquaculture is a relatively small industry, which has made slow progress during its development. Some of the main problems are connected to obtaining viable eggs and juveniles in terms of egg quality, fertilisation rates, and survival through first feeding. There have also been challenges connected to variable growth and flesh pigmentation, early maturation, and marketing. Despite the large volumes of freshwater available in Norway, freshwater fish farming in general, and Arctic charr farming in particular have remained small industries here. One underlying reason are strict environmental regulations connected to freshwater aquaculture in Norway. Parasites may cause harm to Arctic charr aquaculture by reducing growth rates and marketability, as well as causing mortalities in fish held in cages in freshwater. There is little information available on freshwater parasites in southern Norway, as well as parasites threatening Arctic charr aquaculture. The aim of this thesis is to identify challenges, and propose solutions to problems connected to freshwater aquaculture of Arctic charr in southern ...